A novel approach for BCR‐ABL1 standardization to improve International Scale estimation. (27th July 2016) - Maes, B.; Bakkus, M.; Boeckx, N.; Boone, E.; Cauwelier, B.; Denys, B.; De Schouwer, P.; Devos, T.; El Housni, H.; Hillen, F.; Jacobs, K.; Lambert, F.; et al.
Summary: Introduction: Standardization of BCR‐ABL1 messenger RNA quantification by real‐time PCR on the International Scale (IS) is critical for monitoring therapy response in chronic myelogenous leukaemia. Since 2006, BCR‐ABL1 IS standardization is propagated along reference laboratories by calculating a laboratory‐specific conversion factor (CF), co‐ordinated in Europe through the European Treatment and Outcome Study project. Although this process has proven successful to some extent, it has not been achievable for all laboratories due to the complexity of the process and the stringent requirements in terms of numbers of samples to be exchanged. In addition, several BCR‐ABL1 IS quantification methods and secondary reference materials became commercially available. However, it was observed that different IS methods generate consistently different results. Methods: To overcome these difficulties, we have developed an alternative and simple approach of CF calculation, based on the retrospective analysis of existing external quality assessment (EQA) data. Our approach does not depend on the exchange of samples and is solely based on the mathematical CF calculation using EQA results. Results and conclusion: We have demonstrated by thorough statistical validation that this approach performs well in converting BCR‐ABL1 measurements to improve IS estimation. In expectation of a true golden standard method for BCR‐ABL1 IS quantification, the proposed method is a valuable alternative.